The Effect of Price, Product Quality and Promotion on Consumer Buying Interest in the Originote Skincare - Khusnia Amalia Putri; Evi Fitrotun Najiah; Mohammad Yaskun (Jurnal Multidisiplin Sahombu, 2024)
The purpose of this study is to examine the effect of company size and company risk on audit fees in companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2022 period. The total sample used in this study consisted of 224 observations. The dependent variable in this study is audit fees, while the independent variables are company size and company risk. The data were analyzed using multiple linear regression analysis. The results indicate that company size has a significant effect on audit fees because larger companies generally have more complex operational activities, which require more extensive audit procedures and longer audit completion times, thereby increasing audit fees. In addition, company risk also has a significant effect on audit fees because companies with higher levels of risk require auditors to perform more comprehensive audit procedures, resulting in higher audit fees.